Evidence and Potential Mechanisms of Jin-Gui Shen-Qi Wan as a Treatment for Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Hu, Zhipeng; Liu, Xiaoke; Yang, Maoyi (Frontiers in Pharmacology, 2021)
Abstract Background: Type 2 diabetes mellitus (T2DM) is a subtype of diabetes mellitus characterized by progressive dysfunction of β-cell insulin secretion and insulin resistance. Jīn-Guì Shèn-Qì Wán (JGSQW) has for many years been widely used in clinical practice as a treatment for T2DM. However, its effect remains unknown. Objectives: This study aims to summarize clinical evidence on the effect of JGSQW on glucose and lipid metabolism in T2DM and the potential mechanisms underlying this effect. Methods: Six databases were searched without language or publication status restrictions. Data were extracted to a predefined template for synthesis. Results: Fourteen studies with 1586 participants were included in this meta-analysis. All 14 studies were judged to be at high risk of bias. JGSQW is safe for T2DM patients. Pooled results indicated that combination treatment results in a reduction in Glycated hemoglobin (HbA1c) (mean difference (MD) –0.49%; 95% CI –0.67 to –0.31), Fasting blood glucose (FBG) (MD –0.84; 95% CI –1.19 to –0.49) and 2-hour postprandial glucose 2hBG (MD –1.38; 95% CI –1.60 to –1.16). No significant difference in glucose metabolism was observed between JGSQW and hypoglycemic agents. The available evidence was insufficient to determine the effects on lipid metabolism. Sensitivity analyses indicated that these results were robust. Conclusions: By combining the available evidence we found that JGSQW is safe for T2DM patients. Compared with hypoglycemic agents alone, combination treatment with JGSQW enhances the effect on glucose metabolism in patients with T2DM. We found no difference in efficacy of JGSQW alone compared to hypoglycemic agents alone. In terms of lipid metabolism, current evidence is insufficient and too inconsistent for us to draw firm conclusions so further studies are needed.